Chromatic and achromatic contrast sensitivity in the far periphery - Bowers, Norick R.; Gegenfurtner, Karl R.; Goettker, Alexander; Justus Liebig University Giessen (My University, 2025)
The contrast sensitivity function (CSF) has been studied extensively; however, most studies have focused on the central region of the visual field. The current study aims to address two gaps in previous measurements: first, it provides a detailed measurement of the CSF for both achromatic and, importantly, chromatic stimuli in the far periphery, up to 90 dva of visual angle. Second, we describe visual sensitivity around the monocular/binocular boundary that is naturally present in the periphery. In the first experiment, the CSF was measured in three different conditions: Stimuli were either Achromatic (L + M), Red-Green (L − M) or Yellow-Violet (S − (L + M)) Gabor patches. Overall, results followed the expected patterns established in the near periphery. However, achromatic sensitivity in the far periphery was mostly underestimated by current models of visual perception, and the decay in sensitivity observed for red-green stimuli slows down in the periphery. The decay of sensitivity for yellow-violet stimuli roughly matches that of achromatic stimuli. For the second experiment, we compared binocular and monocular visual sensitivity at different locations in the visual field. We observed a consistent increase in visual sensitivity for binocular viewing in the central part of the visual field compared to monocular viewing, but this benefit already decreased within the binocular visual field in the periphery. Together, these data provide a detailed description of visual sensitivity in the far periphery. These measurements can help to improve current models of visual sensitivity and can be vital for applications in full-field visual displays in virtual and augmented reality
Keywords: ddc:150